Clinical outcomes and predictors in patients with previous cardiac surgery undergoing mitral valve transcatheter edge‐to‐edge repair. Issue 3 (29th May 2022) - De Felice, Francesco; Paolucci, Luca; Musto, Carmine; Cifarelli, Alberta; Grasso, Carmelo; Tamburino, Corrado; Adamo, Marianna; Denti, Paolo; Giordano, Arturo; Bartorelli, Antonio L.; Montorfano, Matteo; Citro, Rodolfo; et al.
Abstract: Background: Mitral‐valve transcatheter edge‐to‐edge repair (MV‐TEER) is recommended in patients with severe functional mitral regurgitation (FMR) and in those with degenerative mitral regurgitation (DMR) not eligible to traditional surgery. Patients with a history of previous cardiac surgery are considered at high risk for surgical reintervention, but data are lacking regarding procedural and clinical outcomes. Objective: aim of this study was to assess the efficacy and clinical results of MV‐TEER in patients with previous cardiac surgery enrolled in the "multicentre Italian Society of Interventional Cardiology registry of transcatheter treatment of mitral valve regurgitation" (GIOTTO). Methods: Patients with previous coronary artery bypass grafting (CABG), surgical aortic valve replacement (AVR), or mitral valve repair (MVR) were included. Those with multiple or combined previous cardiac surgeries were excluded. Clinical follow‐up was performed at 30 days, 1 year, and 2 years. The primary endpoint was a composite of death or rehospitalization at 1‐ and 2‐year follow‐ups. Results: A total of 330 patients enrolled in the GIOTTO registry were considered (CABG 77.9%, AVR 14.2%, and MVR 7.9%). Most patients showed FMR (66.9%), moderate reduction of left ventricular (LV) ejection fraction, and signs of LV dilation. Procedural and device successes were 94.8% and 97%. At 1 and 2 years, the composite endpoint occurred are 29.1% and 52.4%, respectively. The composite outcome rates were similar across the three subgroups of previous cardiac surgery ( p  = 0.928) and between the FMR and DMR subgroups ( p  = 0.850) at 2 years. In a multivariate analysis, residual mitral regurgitation (rMR) ≥2+ was the main predictor of adverse events at 1 year (hazard ratio: 1.54 [95% confidence interval,  CI: 1.00–2.38]; p  = 0.050). This association was confirmed at 2 years of Kaplan–Meier analysis ( p  = 0.001). Conclusions: MV‐TEER is effective in these patients, regardless of the subtype of previous cardiac surgery and the MR etiology. An rMR ≥2+ is independently associated with adverse outcomes at 1‐year follow‐up.